2023
DOI: 10.3390/biom13050723
|View full text |Cite
|
Sign up to set email alerts
|

SVM-Based Model Combining Patients’ Reported Outcomes and Lymphocyte Phenotypes of Depression in Systemic Lupus Erythematosus

Abstract: Background: The incidence of depression in patients with systemic lupus erythematosus (SLE) is high and leads to a lower quality of life than that in undepressed SLE patients and healthy individuals. The causes of SLE depression are still unclear. Methods: A total of 94 SLE patients were involved in this study. A series of questionnaires (Hospital Depression Scale, Social Support Rate Scale and so on) were applied. Flow cytometry was used to test the different stages and types of T cells and B cells in periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…NB is rooted in Bayes’ theorem and performs classification by calculating the posterior probabilities of different categories under given feature conditions [ 31 ]. SVM is a supervised learning algorithm that makes predictions by identifying the optimal separating hyperplane [ 32 ]. LR is a linear model that predicts probabilities based on the logistic function [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…NB is rooted in Bayes’ theorem and performs classification by calculating the posterior probabilities of different categories under given feature conditions [ 31 ]. SVM is a supervised learning algorithm that makes predictions by identifying the optimal separating hyperplane [ 32 ]. LR is a linear model that predicts probabilities based on the logistic function [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“… 117 For NPSLE, different T and B cell subsets predicted depression in patients with SLE. 127 128 Proteomics using cerebrospinal fluid demonstrated that CST6, L-selectin, Trappin-2, KLK5 and TCN2 could distinguish NPSLE from SLE controls (non-NPSLE). 124 Other reports using single-cell RNA sequencing data compared biomarkers for NPSLE to multiple sclerosis 103 and vascular dementia.…”
Section: Key Sle Findings By ML Reportsmentioning
confidence: 99%